2018
DOI: 10.1111/jfpe.12892
|View full text |Cite
|
Sign up to set email alerts
|

Solid–liquid extraction of bioactive compounds from yerba mate (Ilex paraguariensis) leaves: Experimental study, kinetics and modeling

Abstract: The aqueous batch extraction of bioactive compounds from yerba mate leaves was evaluated in view of their potential application in the food industry. The influence of temperature (20–80 °C) and stirring (0–400 rpm) was investigated by central composite design. The concentrations of the bioactive compounds over time were investigated using three mathematical models (equilibrium‐dependent, Peleg and intra‐particle diffusion). The results indicated that higher temperatures resulted in increased extraction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Gerke et al determined the best extraction conditions of the raw material to ensure maximum yield and quality of the aqueous extract (30 min, 80 • C, stirring 400 rpm). The beverages obtained under these conditions are characterized by high concentrations of chlorogenic acid, caffeine, and theobromine, at 591.81, 814.90, and 122.56 mg/L, respectively [85]. Similarly, the study by Fenoglio et al demonstrated that spray drying of Yerba Mate extract provided lower moisture content, as well as the highest polyphenol content (135.4 mg GAE/g extract) and oxidative stability compared to freeze-dried samples.…”
Section: Yerba Mate As a Functional Food Ingredientmentioning
confidence: 85%
“…Gerke et al determined the best extraction conditions of the raw material to ensure maximum yield and quality of the aqueous extract (30 min, 80 • C, stirring 400 rpm). The beverages obtained under these conditions are characterized by high concentrations of chlorogenic acid, caffeine, and theobromine, at 591.81, 814.90, and 122.56 mg/L, respectively [85]. Similarly, the study by Fenoglio et al demonstrated that spray drying of Yerba Mate extract provided lower moisture content, as well as the highest polyphenol content (135.4 mg GAE/g extract) and oxidative stability compared to freeze-dried samples.…”
Section: Yerba Mate As a Functional Food Ingredientmentioning
confidence: 85%
“…In addition to them, YM has vitamins such as B2, B1, and C 2,5 . Consequently, it is widely applied in health areas such as pharmaceutical, cosmetological, and alternative medicine 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have been reported on the content of total phenolic compounds and their antioxidant properties in yerba mate leaves [19,20,21,22,23,24]; however, there are few studies related to the extraction kinetics of phenolic compounds in yerba mate leaves and the conditions for their operation on an industrial scale [20,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%